Kerentanan Larva Aedes Aegypti dari Banjarmasin Utara terhadap Temefos - Abdul Gafur; Mahrina Mahrina; Hardiansyah Hardiansyah (Bioscientiae, 2006)
Temephos has been used for more than 25 years in Banjarmasin as a control measure against Aedes aegypti. As long term use of insecticide may lead to resistance, the present study examined susceptibility and resistance of larval Aedes aegypti from Banjarmasin Utara to temephos (Abate 1SG). Larvae were collected from five sites throughout Banjarmasin Utara Subdistrict and were reared to obtain first and second generations for experiments. Larval mortality due to temephos exposure was determined after 24 hours, and probit analyses were applied to determine LC50 and LC99. The results showed that larval susceptibility were similar among sites, except that from Sungai Jingah which was slightly lower in low dose of temephos. LC99 24 hr was 0.0001 mg/l, which was lower than WHO standard for resistance, indicating that that temephos is still effective larvacide against larvae of  Aedes aegypti from Banjarmasin Utara.